Total Quality Management Implementation and Competitive Advantage: The Role of Structural Control and Exploration - Douglas, Thomas J.; Judge, William Q. (Academy of Management Journal, 2001)
The authors explored the relationship between the degree to which total quality management (TQM) practices were adopted within organizations and the corresponding competitive advantages achieved. They found relatively strong support for this relationship. In addition, their data showed some support for the moderating influence of organizational structure on TQM implementation effectiveness. Specifically, two measures of organizational structure, labeled ?control? and ?exploration,? were found to offer independent and interdependent influences on the financial performance of firms implementing TQM programs.